"I love it but I don't use it": students' perceptions on the use of Padlet as an educational tool for learning - Mohd Deni, Ann Rosnida; Zainal, Zainor Izat (2017)
Web 2.0 tools have become ubiquitous in many university classrooms. These tools support collaboration and community building, enhance media sharing, and improve collective knowledge constructions- features that are valuable to learning. Many studies have in fact found that the inclusion of these tools into the teaching and learning processes creates positive learning experiences with many reported preferences of using these tools over traditional methods of learning. This small-scale study which involved 37 undergraduate students, investigated students’ perceptions on the use of a web 2.0 tool, namely Padlet, as an educational tool and students’ frequency of use of and their engagement with it to support their learning of communication concepts. The study, which employed a qualitative approach used two data collection tools: a qualitative questionnaire and analyses of students’ activities on the virtual walls. The study found that even though a small number of students had some negative perceptions of Padlet use, disclosing technical issues, lack of notification and reward, and preference over paper to technology, most of the students perceived Padlet use very positively. Despite this, the study found that most students were only actively engaged with Padlet activities on case-study-related tasks and only prior to assessments but not for independent learning tasks. The study also shows that students’ positive perception of Padlet as a learning tool did not influence students’ frequency of use. Pedagogical strategies are shared to improve the use of Padlet as an educational tool to support students’ learning.